2023
DOI: 10.21118/apgs.v15i1.13689
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida no Teletrabalho Compulsório no Contexto da COVID-19: Percepções entre os Gêneros em Organizações Públicas

Abstract: Objetivo da pesquisa: Analisar os níveis de Qualidade de Vida no Teletrabalho (e-QVT) compulsório durante a pandemia do coronavírus, de servidores públicos brasileiros a partir das percepções entre mulheres e homens e nos perfis segmentados: mulheres e homens com e sem filhos; mulheres com e sem filhos. Enquadramento teórico: Qualidade de Vida no Teletrabalho Compulsório, cujo modelo teórico é composto por cinco dimensões: Atividades do Teletrabalhador; Gestão do Teletrabalho; Suporte Tecnológico; Condições Fí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is important to note that compulsory staying at home represented, for many, compulsory teleworking. Velasco et al (2023) identified compulsory telecommuting as a major source of overload, especially for men and women with children. According to the authors, women and men with children perceive that they are more interrupted during the execution of their activities, who have greater difficulty reconciling personal, professional and leisure life in compulsory teleworking (Velasco et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that compulsory staying at home represented, for many, compulsory teleworking. Velasco et al (2023) identified compulsory telecommuting as a major source of overload, especially for men and women with children. According to the authors, women and men with children perceive that they are more interrupted during the execution of their activities, who have greater difficulty reconciling personal, professional and leisure life in compulsory teleworking (Velasco et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that a part of teleworking will continue even with the end of the pandemic, given the benefits that some organizations are presenting. However, some of the advantages must be analyzed in contrast to the impacts generated by this new reality in the lives of workers (Benavides et al, 2021), especially concerned to possibility of overload in activities that could lead to the risk of illness (Velasco;Oliveira, 2023).…”
Section: Teleworkmentioning
confidence: 99%
“…These data corroborate the findings of Saraiva, Traversini and Lockmann (2020), highlighting the need for teachers to arrange the numerous activities in telework. In addition, there is a greater number of interruptions and reduce the concentration with children at home while carrying out work (Velasco, Pantoja;Oliveira, 2023).…”
Section: Profile Of Professorsmentioning
confidence: 99%